Patients with autosomal dominant spinocerebellar ataxia have more risk of falls, important balance impairment, and decreased ability to function - Carolina Yuri P. Aizawa; Jose Luiz Pedroso; Pedro Braga-Neto; Marilia Rezende Callegari; Orlando Graziani Povoas Barsottini (Arquivos de Neuro-Psiquiatria, 2013)
OBJECTIVES: To assess balance and ability to function in patients with spinocerebellar ataxia. METHODS: A total of 44 patients with different spinocerebellar ataxia types 1, 2, 3, and 6 were evaluated using the Tinetti balance and gait assessment and the functional independence measure. The scale for the assessment and rating of ataxia and the international cooperative ataxia rating scale were used to evaluate disease severity. RESULTS: Most patients showed significant risk of falls. The balance scores were significantly different in spinocerebellar ataxia types. A significant positive correlation between balance and disease severity was found. CONCLUSION: Patients with spinocerebellar ataxia have important balance impairment and risk of falls that influence the ability to function such as self-care, transfers, and locomotion. Furthermore, the more severe ataxia is, the more compromised are postural balance, risk of falls, and ability to function.